Setting times measurements of portland cements with pulsed USWR method - Valič, Marko (Kovine zlitine tehnologije, 1999)
In this paper we present the results of parallel measurements on PC cements; the setting times with a standard Vicat apparatus and the reflection coefficient changes ?$Δ$?r during early hydration with a pulsed ultrasonic shear wave reflection (USWR) hardening meter. The measurements were carried out on the same samples and under the same ambient conditions. In contrast to the Vicat needle test, the USWR method gives continuous information on the stiffening and hardening process over time via ?$Δ$?r changes, as the rigidity of the pastes grow on hydration. The magnitudes of the ?$Δ$?r change in selected cement pastes (CEM I 52.5R and PC 30dz 45s) at Vicat setting times are used to determine the correlation between the two methods. Through such calibration the setting times of production samples can be satisfactorily measured with the USWR method.
Keywords: reološke lastnosti; cement; strjevanje